Design and Implementation of Grounding Resistance Control System Using Water Pump Actuator and Real-Time Monitoring Sensors - gaguk firasanto; Yogi Priyo Istiyono; Nurul Huluq (Program Studi Teknik Elektro Universitas Khairun, 2026)
Grounding system performance is strongly influenced by soil moisture and temperature, which can vary significantly due to environmental conditions. The lack of real-time monitoring may cause grounding resistance to exceed safety limits, particularly during dry seasons. This study aims to design and evaluate a microcontroller-based grounding resistance control system capable of maintaining resistance below 5 Ω through real-time monitoring and automatic soil conditioning. An experimental method was applied at an active grounding installation in the Multi Integra Building, Rawamangun, Jakarta, representing tropical soil conditions with variable moisture content. The proposed system integrates soil moisture and temperature sensors, a microcontroller, and a water pump actuator operating in a closed-loop control scheme. Grounding resistance measurements were conducted before and after automated irrigation and validated using an earth resistance tester. The results show a clear inverse relationship between soil moisture and grounding resistance. Initial dry soil conditions produced an average grounding resistance of 6.095 Ω. After controlled irrigation, soil moisture increased to approximately 63.5% and soil temperature decreased, resulting in a significant reduction of grounding resistance to an average of 0.707 Ω. These findings confirm that active soil moisture control effectively stabilizes grounding performance and enhances electrical safety